Combining intraoperative carmustine wafers and Stupp regimen in multimodal first-line treatment of primary glioblastomas. (August 2015) - Pavlov, Vladislav; Page, Philippe; Abi-Lahoud, Georges; Nataf, François; Dezamis, Edouard; Robin, Audrey; Varlet, Pascale; Turak, Baris; Dhermain, Frédéric; Domont, Julien; Louvel, Guillaume; Souillard-Scemama, Raphaëlle; et al.
Abstract Background. The study investigated if intraoperative use of carmustine wafers, particularly in combination with Stupp regimen, is a viable and safe first-line treatment option of glioblastomas. Methods. Eighty-three consecutive adult patients (50 men; mean age 60 years) with newly diagnosed supratentorial primary glioblastomas that underwent surgical resection with intraoperative carmustine wafers implantation (n = 7.1 ± 1.7) were retrospectively studied. Results. The median overall survival (OS) was 15.8 months with 56 patients dying over the course of the study. There was no significant association between the number of implanted carmustine wafers and complication rates (four surgical site infections, one death). The OS was significantly longer in Stupp regimen patients (19.5 months) as compared with patients with other postoperative treatments (13 months; p = 0.002). In addition patients with eight or more implanted carmustine wafers survived longer (24.5 months) than patients with seven or less implanted wafers (13 months; p = 0.021). Finally, regardless of the number of carmustine wafers, median OS was significantly longer in patients with a subtotal or total resection (21.5 months) than in patients with a partial resection (13 months; p = 0.011). Conclusions. The intraoperative use of carmustine wafers in combination with Stupp regimen is a viable first-line treatment option of glioblastomas. The prognostic value of this treatment association should be evaluated in a multicenter trial, ideally in a randomized and placebo-controlled one.